Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai di Kantor Camat Pendopo Barat Kabupaten Empat Lawang - Yadi Maryadi; Yulia Misrania (UNIVED Press, 2022)
This study aims to determine the effect of organizational culture on employee performance at the West Pendopo sub-district office, Empat Lawang Regency. This type of research is associative research. Data collection techniques used in this study were observation and questionnaires. The type of data used is primary data obtained through questionnaires distributed to 30 respondents, namely employees who work at the West Pendopo Sub-district Office, Empat Lawang Regency. The sampling technique used in sampling is saturated sampling, where the entire population is sampled. The results showed that Organizational Culture had a positive and significant influence on Employee Performance at the Office of the Head of the West Pendopo District of Empat Lawang Regency, from the results of the calculation of the regression equation, namely Y=14,259 + 0.487X, this means that if Organizational Culture is increased by 1 (one) unit then Employee performance increased by 0.487X or 48.7%, hypothesis testing was proven if tcount 2,529 > ttable value 2,04227, so Organizational Culture had a positive and significant effect on Employee Performance at the Office of the Head of the West Pendopo District, Empat Lawang Regency.